Hubungan Perilaku Merokok Konvensional terhadap Saturasi Oksigen pada Pasien General Anestesi di Ruang Intra Anestesi - Fatimah, Fatimah; Elfira, Yenni; Irwadi, Irwadi; Andriyan, Aric Frendi Andriyan; Suherlin, Nicen; Habibudin, Deka (Jurusan Keperawatan Poltekkes Kemenkes Denpasar, 2024)
Smoking that causes pathophysiological changes in almost all parts of the lower respiratory tract including lung organs, inhaled cigarette smoke contains harmful chemicals that can damage the immune system of the respiratory tract so that it can cause disorders of the respiratory tract. Some respiratory system disorders such as airway obstruction, or conditions that can result in airway obstruction, airway infections, and other disorders that can inhibit gas exchange. To determine the relationship of smoking behavior to oxygen saturation in general anesthesia patients in the Intra-Anesthesia Room of Level III Hospital Reksodiwiryo Padang. The type of research is quantitative, with a sample size of 34 respondents using purposive sampling technique. Univariate data analysis is presented in the form of a frequency distribution and bivariate analysis using the chi-square test, data processing using the IBM SPSS version 25.0 computer program. The most age is 26-35 years, which is 17 people (50,0%), the most education is high school, which is 16 people (47,1%), the most jobs are traders, which is 10 people (29,4%), the most conventional smoking behavior is heavy smokers, which is 13 people (38,2%), the most oxygen saturation is abnormal, which is 23 people (67,6%), and there is a relationship between smoking behavior and oxygen saturation in general anesthesia patients in the Intra-Anesthesia Room of Level III Hospital, Reksodiwiryo Padang (p = 0,014). The most age is 26-35 years, the most education is high school, the most jobs are traders, the most conventional smoking behavior is heavy smokers, the most oxygen saturation is abnormal and there is a relationship between smoking behavior to oxygen saturation in general anesthesia patients in the Intra-Anesthesia Room of Level III Hospital Reksodiwiryo Padang